Association of maternal and umbilical cord blood leptin concentrations and abnormal color Doppler indices of umbilical artery with fetal growth restriction - Elahe Zareaan; Mitra Heidarpour; Elham Kargarzadeh (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Fetal growth restriction (FGR) is a condition with heterogeneous pathophysiology which characterized by fetal weight less than the tenth percentile for gestational age. Several factors have impact on maternal, placental and fetal due to growth restriction. Objective: The aim of this study was to investigate the relationship between levels of leptin in the cord, and serum leptin of mothers also abnormal color Doppler indices of umbilical artery with fetal growth restriction. Materials and Methods: This is a cross sectional study conducted in Isfahan, Iran, 2015-2016. We recruited 40 women with singleton pregnancies complicated by fetal growth restriction (Group I) and 40 pregnant women with normal fetal growth (Group II) with matched age. Maternal serum and umbilical artery leptin levels were determined with Enzyme-Linked immunosorben method. Also, color Doppler ultrasound of umbilical artery was performed. Results: Mean maternal and fetal leptin levels were lower in the FGR group compared to the normal group (36.58±(20.99) and 7.42 ±(4.08)vs. 47.32±(22.50) and 30.49±(14.50) respectively). Also, mean fetal leptin level was lower in the group with abnormal color Doppler sonographic indices compared to the normal group (7. 40 ±(4.10)vs 27.06±(15.80), respectively). Conclusion: This study indicated that maternal and fetal leptin levels are correlated with FGR originating from damaged placental function; also fetal leptin level can indicate changes in color Doppler sonographic indices.